1988
DOI: 10.1016/0022-4375(88)90044-8
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory seat belt laws in eight states: a time-series evaluation

Abstract: We examined state-specific and aggregate effects of U.S. legislation requiring the use of seat befts among front-seat motor vehicle occupants. Effects of compulsory seat belt use on the number of occupants fatally injured in traffic crashes were examined in the first eight states adopting such laws. Monthly data on crash fatalities between January 1976 and June 1986 were analyzed using Box-Tiao intervention analysis time-series methods. Because the new laws apply only to front-seat occupants, front-seat occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…Other research has found that safety belt use in the United States has increased substantially since the mid-1980s in the general population (Nelson, Bolen, & Kresnow, 1998), but the degree to which adolescents are responsive to such laws is not known. Research has also found that belt laws resulted in significant overall reductions in car crash fatalities (Wagenaar, Maybee, & Sullivan, 1988) and injuries (Wagenaar & Margolis, 1990). The data analyzed in the present study provide an opportunity to assess potential differential effects of the laws on subgroups of adolescents who differ on sociodemographic characteristics, as well as on risk-taking behaviors.…”
Section: Introductionmentioning
confidence: 80%
“…Other research has found that safety belt use in the United States has increased substantially since the mid-1980s in the general population (Nelson, Bolen, & Kresnow, 1998), but the degree to which adolescents are responsive to such laws is not known. Research has also found that belt laws resulted in significant overall reductions in car crash fatalities (Wagenaar, Maybee, & Sullivan, 1988) and injuries (Wagenaar & Margolis, 1990). The data analyzed in the present study provide an opportunity to assess potential differential effects of the laws on subgroups of adolescents who differ on sociodemographic characteristics, as well as on risk-taking behaviors.…”
Section: Introductionmentioning
confidence: 80%
“…5 Scaling up using a vertical approach involves the introduction of an intervention simultaneously across a whole system and results in institutionalisation of a change through policy, regulation, financing or health systems. Examples of successful vertically scaled up interventions include the introduction of mandatory seatbelt legislation 15 , smoking bans in outdoor eating areas 16 and the introduction of new health system financing models. 17 Scaling up using a horizontal approach involves the introduction of an intervention across different sites or groups in a phased manner, often beginning with a pilot program, followed by stepwise expansion, learning lessons along the way to help refine further expansion.…”
Section: Monitor Performance and Efficiencymentioning
confidence: 99%
“…41 After controlling for state and year fixed effects, Michener and Tighe (1992) find the number of fatal accidents in 1989 would have been reduced by 1.9% with nationwide secondary seatbelt laws and by 9% with 41 Others using time-series data from before and after a seatbelt law was passed include Bhattacharyya and Layton (1979), Harvey and Durbin (1986), and Wagenaar et al (1988 A few studies have looked at the direct effect of seatbelt wearing rates on traffic fatalities (Garbacz, 1990(Garbacz, , 1991McCornac, 1993;Risa, 1994;Noland, 2003b), but Cohen and Einav (2003) seem to be the first to account for the endogeneity of the seatbelt usage variable-i.e., people wearing seatbelts more often on roads known to be more dangerous. The failure to control for this endogeneity could be the reason that Garbacz (1990Garbacz ( , 1991 and Risa (1994) find fatalities to increase with seatbelt usage.…”
Section: 22c Seatbelt Laws and Seatbelt Usagementioning
confidence: 99%